Evapotranspiration From Wheat Under Semi-Arid Conditions in Punjab - Hundal, S S; Sandhu, B S; Singh, Rajwant (Annals of Arid Zone, 2016)
Actual evapotranspiration (AET) frem whea t irrigated at IW/CPE ratio of 1.0 was measured daily (rom the weighing Iysimeter during rabi 1985-86 and 1986-87. Evaporation (Ep) from USWB class A pan evaporimeter, and potential evapotranspiration calculated by the modified Penman method were compared with AET. The crop season AET amounted to 316 mm in the first and 309 mm in the second year. The AET was found to be 30 mm from sowing to crown root initiation (CRI), 27-40mm from CRI to jointing. 60-80 mm;from jointing to heading, 136-146 m:n from heading to dough, and 31-45 mm from dough to maturity stages of crop growth during the two-year period. Both PET and Ep remained higher than AET during initial 6 to 7 weeks and again 3 to 4 weeks before harvest. However, AET remained slightly higher than PET and Ep during the maximum growth stage of the crop. Wheat crop resulted in wat:r use efficiency of 11.3 and 13.3 kg grain/ha/mm of water during 1985-86 and 1986-87, respectively.